P186 Surgical treatment of vulvar cancer: impact of tumor-free margin distance on recurrence and survival. A multicentre cohort analysis from the francogyn study group. (1st November 2019) - Raimond, E; Delorme, C; Ouldamer, L; Carcopino, X; Bendifallah, S; Touboul, C; Daraï, E; Ballester, M; Graesslin, O
Abstract : Introduction/Background: In vulvar cancer, it is admitted that tumor-free margin distance is one of the most important element for locoregional control. It is currently recommended to surgically remove the tumor with at least an 8 mm tumor-free margin. The aim of this study was to evaluate the impact of tumor-free margin distance on recurrence and survival in vulvar cancer. Methodology: From 2005 to 2016, 112 patients surgically treated for a vulvar squamous cell cancer were included in a retrospective multicenter study. Overall, disease-free and metastasis-free survivals were analyzed according to tumor-free margin distance. Results: Patients were divided into three groups : group 1 (margin <3 mm, n=47) ; group 2 (margin ≥3 mm to <8 mm, n=48) and group 3 (margin ≥8 mm, n=17). During the study, 26, 8% patients developed recurrence (n=30) after a median of 8 months (1–69). Analysis of 5-year overall survival, as well as disease-free and metastasis-free survivals, did not reveal a difference between groups. We performed a subgroup analysis in patients with a tumor-free margin <8 mm (group 1 and 2). It showed that histological lesions observed closest to the edge of the specimen were more often invasive or in situ carcinoma lesions in group 1 than in group 2, in which VIN lesions were mainly observed at this location. After re-excision, no patients in group 1 and 50% (n=2) patients in group 2 developed recurrence. Conclusion: This study did not reveal a significant impact of tumor-free margin distance on recurrence and survival in vulvar cancer. Moreover, the benefit of re-excision seems stronger when tumor-free margins are positive or very close (<3 mm), cases in which invasive or in situ lesions are often present closest to the edge of the specimen. Disclosure: Nothing to disclose.